Pengaruh Pendapatan Asli Daerah dan Dana Bagi Hasil terhadap Pertumbuhan Ekonomi dan Indeks Pembangunan Manusia di Kabupaten Kutai Timur - Alfrida Karampuan; Rahcmad Budi Suharto; Diana Lestari (Jurnal Riset Ekonomi dan Akuntansi, 2023)
This study aims to analyze and determine the effect of regional original income and profit-sharing funds on economic growth and development index in East Kutai Regency. The analysis tool used is path analysis. The data used is secondary data in 2005-2023. The results of path analysis 1, Local Own Revenue has no effect on economic growth, while Profit Sharing Funds have a negative and significant effect on economic growth and Regional Own Revenue and Revenue Sharing Funds have an effect simultaneously on economic growth. Results of path 2 analysis, Regional Own Revenue has no effect on the human development index, profit sharing has a negative and significant effect on the human development index, and economic growth has no effect on the human development index as well as Local Own Revenue and Profit Sharing Funds as well as economic growth simultaneously influencing the Human Development Index, Indirectly Original Income Regions do not affect the Human Development Index through economic growth, while Revenue Sharing Funds indirectly affect the Human Development Index through economic growth